Acceptability of the Moyo device for intrapartum fetal heart rate monitoring at a referral hospital in Uganda: a qualitative study - Milton W. Musaba; Ritah Nantale; Julius N. Wandabwa; Agnes Napyo; Albert Ssesanga; Usaama Ssewankambo; Akello Eunice; Kenneth Mugabe; Brendah Nambozo; Faith Oguttu; John Stephen Obbo; Andrew D. Weeks; et al. (BMC Pregnancy and Childbirth)
Abstract Background The Moyo device is an easy-to-use device that allows continuous electronic fetal heart rate monitoring (FHRM). We explored the acceptability of using the Moyo device for continuous intrapartum FHRM in Eastern Uganda. Methods Between November 2023 and August 2024, we introduced the Moyo device for continuous intrapartum FHRM among mothers with high-risk pregnancies at Mbale Regional Referral Hospital in Eastern Uganda. We then conducted 34 in-depth interviews with 14 health workers who had used the Moyo device for continuous FHRM and with 20 mothers on whom the Moyo device was used. Participants were purposively selected and interviewed using a semi-structured interview guide. The interviews were audio recorded and transcribed verbatim. We analyzed data using thematic content analysis in Atlas ti.9 software and presented our findings using Sekhon’s acceptability model. Results Participants perceived the Moyo device as a useful and an easy-to-use tool for intrapartum FHRM. Mothers felt involved in monitoring their babies’ condition, with the freedom to ambulate during labour. Moyo facilitated early detection of fetal distress, and triage of patients awaiting caesarean section in a very busy setting. The facilitators to its use were: adequate staff training, health education and counselling of mothers about the device, and tool attributes such as accuracy, reliability and being user friendly. The barriers included poor health worker attitudes, risk of cross-infection, short battery life and the device alarms that were perceived as disturbances. Conclusion The Moyo device was acceptable to both health workers and mothers, with perceived improvements in both obstetric outcomes and birth experience. When introducing the device, careful attention needs to be paid to the training of both staff and the laboring women. Potential success of large scale roll out is supported by participants’ positive attitudes toward the Moyo and high perceived effectiveness.